Integrated economic and environmental modeling of forest biomass for renewable energy in California: Part I - Model development. (June 2023) - Li, Kaiyan; Kirkland, Scott; Yeo, Boon-Ling; Tubbesing, Carmen; Bandaru, Varaprasad; Song, Lan; Holstege, Laura; Hartsough, Bruce; Kendall, Alissa; Jenkins, Bryan
Abstract: Forests are a major natural resource of the state of California, where over a third of the land is forested, and provide a wide range of environmental, economic, and social benefits. Over the past decade, unprecedented drought, insect outbreaks and wildfires have resulted in large-scale tree mortality that greatly affects the forest ecosystem and poses significant threat to human health and welfare and to the environment. Forest thinning and management is considered imperative to improve forest health and resilience. Forest resources including dead and dying trees as well as the residues produced from forest thinning and timber harvesting operations could potentially be used to a greater degree than at present to generate electricity and other renewable energy to meet the increasing demand for more sustainable supplies and mitigate the risk of wildfires. However, efforts to construct new electricity generation capacity in the state at any scale over the last several decades have faced both economic and environmental challenges. As needs for alternative management approaches have become clear, opportunities have emerged for new bioenergy projects. These projects need to be effectively planned and potential economic and environmental performance carefully evaluated. Toward this purpose, an integrated framework model for lifecycle and technoeconomic assessment was developed to quantify environmental and economic impacts, initially for generating electricity using forest resources and with associated web services developed for an online application (forestdss.ucdavis.edu ) that allows potential users to quickly estimate the economic and environmental performance of a potential facility at specified locations. Highlights: Tree mortality, past fire suppression practices, and high fuel loadings threaten forests and human health and welfare. Forest resources including dead and dying trees as well as residues can be used for greater renewable energy production. Bioenergy projects need to be effectively planned and potential economic and environmental performance carefully evaluated. An integrated spatial framework model was developed to aid in decision making related to new project investments.